Guz olbrzymiokomórkowy - opis przypadku = Giant cell tumor - case report - Białkowska-Głowacka, Jolanta; Janas-Naze, Anna; Milner, Paweł; Osica, Piotr; Ratajek-Gruda, Monika (Journal of Education, Health and Sport, 2016)
Białkowska-Głowacka Jolanta, Janas-Naze Anna, Milner Paweł, Osica Piotr, Ratajek-Gruda Monika. Guz olbrzymiokomórkowy - opis przypadku = Giant cell tumor - case report. Journal of Education, Health and Sport. 2016;6(1):27-37. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.44562 http://ojs.ukw.edu.pl/index.php/johs/article/view/44562 http://pbn.nauka.gov.pl/works/690317 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.12.2015. Revised 25.12.2015. Accepted: 09.01.2016. Guz olbrzymiokomórkowy - opis przypadku Giant cell tumor - case report Jolanta Białkowska-Głowacka, Anna Janas-Naze, Paweł Milner, Piotr Osica, Monika Ratajek-Gruda Zakład Chirurgii Stomatologicznej Uniwersytetu Medycznego w Łodzi Kierownik: dr hab. n. med., prof. nadzw. Anna Janas-Naze Adres do korespondencji: dr n. med. Piotr Osica Zakład Chirurgii Stomatologicznej UM w Łodzi 92-213 Łódź, ul. Pomorska 251 mail: piotr.osica@umed.lodz.pl Praca finansowana przez UM w Łodzi w ramach działalności statutowej nr 503/2-163-01/503-21-001. Streszczenie W pracy przedstawiono przypadek pacjentki u której obserwowano przez kilka miesięcy zmianę na błonie śluzowej szczęki, bez weryfikacji diagnostycznej. Podkreślono jak ważną rolę pełni lekarz stomatolog w monitorowaniu zmian w jamie ustnej, przedstawiono niektóre metody diagnostyczne niezbędne do ustalenia rozpoznania. Słowa kluczowe: guz olbrzymiokomórkowy, badanie histopatologiczne, diagnostyka. Summary The article describes a case of a patient, in which over a few months period, a lesion on the maxillary mucosa has been observed, without earlier histopathological verification. The important role of a dentist in monitoring the lesions in oral cavity has been underlined. The authors discuss also certain diagnostic methods, necessary for confirming the diagnosis. Key words: giant cell tumor, histological examination, diagnosis.